Grasshopper Nematode: Mermis nigrescens Dujardin, 1842 - John L. Capinera (EDIS, 2011)
These large nematodes can sometimes be seen leaving grasshoppers, especially those that have been injured. On rainy mornings in spring or summer they can be found depositing their eggs on leaves for grasshoppers to eat. Because they are so large (up to 160 mm or about 6 inches in length), they attract attention. Learn more in this 5-page fact sheet written by John L. Capinera and published by the UF Department of Entomology and Nematology, August 2011. Reviewed August 2014.